Regionalna identiteta mladih v Zasavju - Marot, Naja (Geografski vestnik, 2005)
After two hundred years of economic bloom, Zasavje has found itself in a crisis comprised of many developmental problems, including a very pessimistic outlook of the region's inhabitants. Based on conducted research, this article aims to determine borders, characteristics and identity of the region, focusing on young people as the most important group for future development. It is founded on Paasi's theory of regional identity, which is divided into identity of a region and regional consciousness. Each can be discussed through individual elements. Both are important for actual definition of the region as it is perceived by its inhabitants. Based on gathered data and results, the article provides some basis and an outline of future development of the narrower, statistical, or wider, developmental region Zasavje.
Keywords: Slovenia; Slovenija; Zasavje; Central Sava Valley; regionalni razvoj; regional geography; regionalna geografija; regionalna identiteta